A review of the role of intravitreal corticosteroids as an adjuvant to antibiotics in infectious endophthalmitis - Ho, Dawn Ching Wen (2020)
Infectious endophthalmitis is an important cause of vision loss worldwide. This entity most often occurs as a complication of intraocular surgery especially following cataract surgery or intravitreal injection. Endophthalmitis is regarded as a serious complication following ocular surgery and the final visual outcome is fundamentally contingent on timely recognition and intervention. Intravitreal and oral antibiotics in combination with pars plana vitrectomy or vitreous aspiration remain the mainstay in the management of endophthalmitis. However, significant inflammation may persist even after sterilization of the intraocular cavities with appropriate antibiotics resulting in failure of treatment. This forms the basis for the use of intravitreal corticosteroids as an adjuvant to antibiotics in the management of infectious endophthalmitis. In the index manuscript, we review the existing literature to determine the role of intravitreal corticosteroids as an adjuvant to antibiotics in treating infectious endophthalmitis, and discuss their beneficial effects and controversial concerns.